A BIBLIOMETRIC ANALYSIS OF TECHNOLOGICAL INTELLIGENCE IN CORPORATE MANAGEMENT - Zakaria, Rian; Anridho, Nadia (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This study synthesizes the rapidly expanding literature on technological intelligence in corporate management to provide a comprehensive theoretical synthesis of its intellectual boundaries. A rigorous bibliometric analysis of 890 articles published between 2000 and 2024 was conducted using VOSviewer and the bibliometrix package to assess conceptual evolution and structural networks. Empirical findings reveal a pronounced paradigm shift from early operational efficiency frameworks toward a contemporary emphasis on digital governance, financial technology, and responsible innovation. The primary scholarly contribution of this research lies in mapping the critical conceptual gap between advanced digital technologies, such as artificial intelligence, blockchain, and corporate sustainability. Network analyses demonstrate that while operational technology adoption dominates the current discourse, theoretical integration with environmental, social, and governance (ESG) paradigms remains fundamentally underexplored. This review ultimately establishes a novel conceptual roadmap for future research, highlighting the urgent need for interdisciplinary frameworks that align technological intelligence with governance integrity and sustainable corporate performance.